Losing Insurance and Behavioral Health Hospitalizations: Evidence from a Large-Scale Medicaid Disenrollment - J. Catherine Maclean; Sebastian Tello-Trillo; Douglas A. Webber (Institute of Labor Economics (IZA), 2019)
We study the effects of losing insurance on behavioral health – mental health and substance use disorder (SUD) – community hospitalizations. We leverage variation in public insurance eligibility offered by a large-scale Medicaid disenrollment. Losing insurance decreased SUD-related hospitalizations but mental illness hospitalizations were unchanged. Use of Medicaid to pay for behavioral health hospitalizations declined post-disenrollment. Mental illness hospitalization financing shifted to private insurance, Medicare, and patients, while SUD treatment financing shifted entirely to patients. We investigate implications of reliance on data that is not representative at the level of the treatment variable and propose a possible solution.
Keywords: I1; I11; I18; 330; healthcare; community hospitalizations; insurance; mental illness; substance use disorders; data quality